ANALISIS PENGARUH KOMPENSASI, PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. SANTOS JAYA ABADI SIDOARJO - Lintang Sunarto; Sri Rahayu; Pompong B Setiadi (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to analyze the influence of compensation, career development, and work environment on employee performance at PT. Santos Jaya Abadi Sidoarjo. The research was conducted using a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to 100 employees selected using simple random sampling techniques. The collected data were analyzed using validity and reliability tests, multiple linear regression analysis, coefficient of determination, as well as simultaneous and partial hypothesis testing with the help of SPSS 21.0 software. The results showed that compensation, career development, and work environment had a positive and significant effect on employee performance both partially and simultaneously. Compensation was identified as the most dominant variable influencing employee performance. The coefficient of determination indicated that the three independent variables contributed significantly to employee performance. The findings imply that companies need to improve compensation systems, career development opportunities, and work environment quality to enhance employee productivity and organizational performance. This research contributes to the development of human resource management studies, particularly in manufacturing companies in Indonesia.